PENGARUH ORGANISASI PEMBELAJARAN TERHADAP KINERJA TIM PADA BAGIAN SEKRETARIAT KABUPATEN SIGI - Syukur, Syukur (Katalogis, 2016)
The purpose of this research was to determine and analyze the influence of the learning organizational consisting of organizational learning, learning at workplace, learning climate and learning structure on the performance of the team simultaneously and partially in the Secretariat Section of Sigi District. This is a causal descriptive research with a survey approach using 74 employees as the sample with sampling technique used Proportional Random Sampling. Data were analyzed using multiple linear regression analysis and the results show that learning organizational variable (X) consisting of organizational learning (X1), learning at the workplace (X2), a learning climate (X3) and the structure of learning (X4) simultaneously give a positivr and significant impact on the performance of the team in Secretariat Section of Sigi District, with a value of F counted 23.826 > F-table value of 1.53 or the Sig-F 0.000 < Î± value 0.05. Variable of organizational learning, learning at workplace, learning climate and learning structure partially give positive and significant impact on the performance of the team in Secretariat Section of Sigi District with t counted respectively 5.119; 2.486; 2.029; and 2.369 > 2.000 t-table value or value of sig-t respectively 0.000; 0.015; 0.003; and 0.021 < Î± value 0.05 at the 95% confidence level.